Lagrangian description of the partially massless higher spin N = 1 supermultiplets in AdS4 space; Journal of High Energy Physics; Vol. 2019, iss. 8 - Bukhbinder I. L. Iosif Lvovich; Khabarov M. V. Maxim; Snegirev T. V. Timofey Vladimirovich; Zinovjev Yu. M. Yury Mikhaylovich (2019, 2019)
Title screen